Experience of pregnancy and maternity by adolescents/young people born infected with HIV - Clarissa Bohrer da Silva; Maria da Graça Corso da Motta; Renata Bellenzani (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to understand the experience of pregnancy and motherhood by adolescents/young people who were born infected with HIV. Method: we carried out a qualitative study specialized in HIV service in Porto Alegre (RS/Brazil). Ten adolescents/young people were interviewed from June 2017 to March 2018. Thematic analysis was performed, using a vulnerability framework to reflect about unplanned pregnancy and its implications for care. Results: four categories were highlighted: Discovery of the ongoing pregnancy: ambivalent feelings towards seropositivity; Breaking the news of the pregnancy to partner, family and health professionals; Experience of childbirth and prophylaxis of vertical transmission of HIV; and Experience of motherhood: implications for life stories and future projects. Final considerations: the study contributes to addressing situations of vulnerability to the occurrence of unplanned pregnancy, showing the need for dialogical proposals that respect human rights in the production of comprehensive care and reproductive planning.